Implementation of Digital-Based Public Information Disclosure Services in Tanjungpinang City - Diko Ardiansyah; Nur Aslamaturrahmah Dwi Putri; Ardi Putra (Post Graduate School of Government Science, 2026)
Digital public information services delivered through local government information and documentation portals are expected to improve transparency, yet implementation can remain uneven in practice. This This study examines the implementation of public information service policy through the information and documentation portal managed by the Communication and Informatics Office of Tanjungpinang City. The study applies George C. Edward III's policy implementation framework, covering communication, resources, disposition, and bureaucratic structure. A descriptive qualitative approach was used, with nine purposively selected informants comprising the head of the office, portal administrators, an implementing unit administrator, and service users. Data were collected through in- depth interviews, direct portal observation, and documentation, then analysed using the interactive model of Miles and Huberman and validated through source and technique triangulation. The findings show uneven implementation: information reaches users through multiple channels, but some application requirements are incomplete or inconsistent; personnel and budget are limited; local officers have limited technical authority because the platform is centrally controlled; officer disposition supports service responsiveness; and coordination across regional units remains fragmented. The study concludes that Edward III's framework remains useful but requires contextual extension in digital government, where technical authority and platform ownership can condition local implementation capacity and digital service continuity.